2016
DOI: 10.1111/jomf.12336
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Boomerang Fathers in Adolescent Female Depression

Abstract: Data from the 1979 National Longitudinal Survey of Youth were employed to explore the association between boomerang fathering from birth to age 18 on adolescent depressive symptomatology (N = 3,731). We examined the effects of experiencing a biological father exiting and entering the home because of breaking up and repartnering with an adolescent's mother (i.e., “boomerang fathering”) when compared with other father residential patterns on adolescent depression. Findings suggest that boomerang fathering is mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 71 publications
0
8
1
Order By: Relevance
“…In keeping with previous research that examined the association between cohabiting parents' relationship churning and 9‐year‐old children's outcomes (Nepomnyaschy & Teitler ), we did not see differences between adolescents with churning parents and adolescents with stably together parents once we accounted for demographic and socioeconomic characteristics associated with parental relationships. Our findings contrast with a study of an earlier cohort of churning parents, in which girls (but not boys) in churning families reported fewer depressive symptoms than those in families in which parents stably broke up (Hernandez et al, ). We did not find gender differences in our more recent sample, and we found that it is youth whose parents stably separate who show more positive outcomes than those from churning families.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In keeping with previous research that examined the association between cohabiting parents' relationship churning and 9‐year‐old children's outcomes (Nepomnyaschy & Teitler ), we did not see differences between adolescents with churning parents and adolescents with stably together parents once we accounted for demographic and socioeconomic characteristics associated with parental relationships. Our findings contrast with a study of an earlier cohort of churning parents, in which girls (but not boys) in churning families reported fewer depressive symptoms than those in families in which parents stably broke up (Hernandez et al, ). We did not find gender differences in our more recent sample, and we found that it is youth whose parents stably separate who show more positive outcomes than those from churning families.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, another study using a sample of teens born predominantly in the 1980s finds that teenage girls (but not boys) in stably together or churning families reported a lower incidence of depressive symptoms when compared with those in other family forms (Hernandez et al, ). We extend this research by using a contemporary data source with a more racially/ethnically and socioeconomically heterogeneous sample and by considering a wider range of outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heightened parenting stress, therefore, could be due to the fact that more-intensive parenting efforts are occurring in the context of a more ambiguous and volatile “package deal.” Churning could have a protective effect in terms of keeping fathers involved longer or more intensively than they would be if the couple had broken up and started relationships with new partners (rather than reuniting with each other). Moving beyond father involvement, future research should examine whether and how this relationship form—churning—has implications for parental and child well-being (see, for example, Hernandez et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Yet it is important that studies continue to distinguish between marital and cohabiting unions in their analyses because as cohabitation becomes more commonplace, especially among emerging adults, it may become more or less distinguishable from marriage. Recent research also emphasizes the importance of considering past cohabitations/marriages in analyses of union status and body weight (Hernandez, Pressler, & Dorius, 2011), as only counting current status misses past transitions that may have had lasting effects on body weight and/or that may alter behavior in subsequent cohabitations/marriages.…”
Section: Union Status and Bmimentioning
confidence: 99%